The Penta-Helix Approach in Implementing the Policy of Revitalizing Traditional Markets in Tanjungpinang City - Yudithia, Yudithia; Yafi, Eiad; Khan, Muhammad Shahid (CV. Austronesia Akademika, 2024)
Traditional markets are crucial centers for trade and economic activities within the community. However, the rise of modern markets has led to a decline in the popularity of traditional markets among the public. Therefore, revitalization policies for traditional markets are necessary to enhance their quality and provide significant benefits to the community. This study employs a descriptive qualitative research method with a post-positivist approach. The findings indicate that the Penta-Helix approach is effective in implementing revitalization policies for traditional markets in Tanjungpinang City. The Penta-Helix model can engage five key actors: the government, industry, academia, society, and media, in formulating, executing, and evaluating the revitalization programs for traditional markets in Tanjungpinang. The impact of revitalizing traditional markets in Tanjungpinang is quite significant, including increased visitor numbers, improved environmental health, enhanced product quality, job creation, and heightened community pride in their traditional markets. The implementation of revitalization policies involves reorganizing merchandise, providing cleaning services, controlling product quality, developing local products, and introducing derivative programs. Strong support and commitment from local government and all stakeholders are essential in overcoming challenges such as political factors, limited resources, and a lack of public awareness. Recommendations emphasize the need for proactive efforts and active roles from local government and all stakeholders in executing effective and sustainable policies.